Breeding biology of feral Greylag Geese in south-west Scotland - Young, John G (Wildfowl, 1972)
Greylag Geese Anser anser were reintroduced to south-west Scotland about 1930 and by 1971 the population was estimated at over 1,000. They prefer to nest on wooded islands in a variety of sites. Laying and hatching dates were consistent from year to year. Old nest sites are re-used and most females lay four to six eggs. Some clutches are by two females and bigamy was proved. Incubation is by the female alone and lasts 29 days. The behaviour during incubation is described. Eggs are smaller than those of Continental Greylags but indistinguishable from those collected in Iceland. They hatch at any time of day and the goslings weigh on average 127 grams. There is no significant natural predation. Repeated brood size counts indicate good gosling survival compared to the Icelandic population.